Groundwater quality in an upland agricultural watershed in the sub-humid Ethiopian Highlands - Akal, Adugnaw T.; Dagnew, D.C.; Giri, S.; Belete, M.A.; Tilahun, Seifu A.; Mekuria, Wolde; Steenhuis, Tammo S. (Scientific Research Publishing, Inc., 2017)
Agricultural intensification to meet the food needs of the rapidly growing population in developing countries is negatively affecting the water quality. In most of these countries such as Ethiopia, information on surface and especially groundwater quality is lacking. This limits the measure that can be taken to stop pollution. We, therefore, investigated the spatial and temporal variation of groundwater quality in the upland watershed. Tikur-Wuha watershed was selected because it is located in the Lake Tana watershed, which is seeing the first signs of eutrophication. Groundwater samples were collected from July 2014 to June 2015 from 19 shallow wells located throughout the watershed. Collected water samples were analyzed both in situ and in the laboratory to determine pH, electric conductivity (EC) and total dissolved solid (TDS), concentration of chemicals (nitrate, dissolved phosphorus, calcium, magnesium, aluminum and iron) and Escherichia coli (E. coli). We found that shallow groundwater had greater chemical concentrations and E. coli level in the monsoon rain phase than in the dry phase. Wells located down slope exhibited greater concentrations than mid- and upper-slope positions, with the exception of the nitrate concentration that was less down slope, due to denitrification in the shallow groundwater. Only E. coli level was above the WHO drinking water quality standards. Further studies on groundwater quality should be carried out to understand the extent of groundwater contamination.